2019
DOI: 10.3390/en12193640
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerability of the Power Sector to Climate Variability and Change: Evidence from Indonesia

Abstract: The power sector is a key target for reducing CO2 emissions. However, little attention has been paid to the sector’s vulnerability to climate change. This paper investigates the impacts of severe weather events and changes in climate variables on the power sector in developing countries, focusing on Indonesia as a country with growing electricity infrastructure, yet being vulnerable to natural hazards. We obtain empirical evidence concerning weather and climate impacts through interviews and focus group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…This supports the assertion of [39] that type of business will influence the level of investment to mitigate business risk. Likewise, this tally with the findings of [40] in Indonesia, that the quantum of investment in the power sector of Indonesia enhances the Indonesian government's mitigation of climate variability. Most limited liability and partnership SMEs will be willing to spend more money to mitigate business risks, such as climate change's effect on their business, than sole proprietor SMEs [6].…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 65%
“…This supports the assertion of [39] that type of business will influence the level of investment to mitigate business risk. Likewise, this tally with the findings of [40] in Indonesia, that the quantum of investment in the power sector of Indonesia enhances the Indonesian government's mitigation of climate variability. Most limited liability and partnership SMEs will be willing to spend more money to mitigate business risks, such as climate change's effect on their business, than sole proprietor SMEs [6].…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 65%
“…Damage to urban transmission and distribution networks can lead to a resilience reduction in power transmission capacity, reducing urban energy resilience. For instance, a large-scale blackout occurred in Australia, 2016 [40] , which is caused by windstorm and accompanying extreme weather.…”
Section: Resilient Urban Power Gridmentioning
confidence: 99%
“…Then the research discussing biofuels also found that the government can utilize financial engineering to advance the bioethanol program by utilizing excise and subsidy instruments (Purwoko, 2019) as a continuation of the change in the direction of energy management to renewable energy which is the result of massive energy consumption and mass production of carbon emissions, keywords such as global warming, gas emissions also appear. It is about weather that occurs due to global warming also affects the electricity sector (Handayani et al, 2019), and how the transportation sector also contributes greatly to gas emissions (Setiawan et al, 2019).…”
Section: A) Mapping Of Energy Policy Research Trends In Indonesiamentioning
confidence: 99%